Speaking of Monsters - Picart, Caroline Joan S. author. aut Link
XVI, 326 p.
Keywords: Employing a range of approaches to examine how "monster-talk" pervades not only popular culture but also public policy through film and other media, this book is a "one-stop shop" of sorts for students and instructors employing various approaches and media in the study of "teratologies," or discourses of the monstrous.